Complete regularity of paratopological gyrogroups - Watchareepan Atiponrat (2020)
© 2019 Elsevier B.V. In this work, we explore properties related to the separation axioms and show that every regular paratopological gyrogroup equipped with some mild conditions is completely regular. We also provide some examples supporting our results.